Aesthetics in Eje Festival at Ode Irele. Issue 1 (1st July 2018) - Omosule, Segun
The nature of Eje Festival in relation to gender is the subject of this study. The study deploys the tool of aesthetic as an instrument to particularly investigate the role of masquerades as a means of entertaining female members of the community periodically. Dwelling on aesthetics as a critical tool, the study unravels the performance of Eje Festival as a means of solving some perceived agrarian problems. The study concludes that the underlying reason behind the festival is subsumed in the quest for entertainment and the need for cohesion in the society especially as a means of enhancing the safety of members who might be married to people far and near.